2016
DOI: 10.1021/acs.chemmater.6b02424
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights and 3D Diffusion Pathways within the Lithium Superionic Conductor Li10GeP2S12

Abstract: Inspired by the ongoing debate about the ion dynamics in the lithium superionic conductor Li 10 GeP 2 S 12 (LGPS), we present neutron powder diffraction data in combination with analyses of differential bond valence and nuclear density maps to elucidate the underlying diffusion pathways in Li 10 GeP 2 S 12 . LGPS exhibits quasi-isotropic three-dimensional lithium diffusion pathways, which is a combination of one-dimensional diffusion channels crossing two diffusion planes. Furthermore, ultrasonic speeds of sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
246
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(273 citation statements)
references
References 53 publications
(158 reference statements)
23
246
1
Order By: Relevance
“…Over the last couple of years some breakthroughs have, however, been reported. As an example, in 2011 Kanno and co-workers reported on extremely high ionic conductivity σ ion of 1.7 × 10 −2 S cm −1 for Li 10 GeP 2 S 12 [35] which exhibits quasi-isotropic three-dimensional lithium diffusion pathways [60]; for Li 7 P 3 S 11 , on the other hand, Seino et al [52] showed that in heat-treated and highly dense Li 7 P 3 S 11 σ ion can reach values up to 1.7 × 10 −2 S cm −1 at room temperature, too. The same holds for Li 7 P 3 S 11 that was prepared through spark plasma sintering [61].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last couple of years some breakthroughs have, however, been reported. As an example, in 2011 Kanno and co-workers reported on extremely high ionic conductivity σ ion of 1.7 × 10 −2 S cm −1 for Li 10 GeP 2 S 12 [35] which exhibits quasi-isotropic three-dimensional lithium diffusion pathways [60]; for Li 7 P 3 S 11 , on the other hand, Seino et al [52] showed that in heat-treated and highly dense Li 7 P 3 S 11 σ ion can reach values up to 1.7 × 10 −2 S cm −1 at room temperature, too. The same holds for Li 7 P 3 S 11 that was prepared through spark plasma sintering [61].…”
Section: Introductionmentioning
confidence: 99%
“…Li4 connects the Li3 − [Li1 − Li1] − Li3 diffusion channels along c and opens up the possibility for Li diffusion also in the a-b plane. Indeed, Janek, Zeier and co-workers [71] confirmed the significant contribution of the in-plane Li diffusion (along Li3 − [Li2 − Li2] − Li3 and Li4 − [Li1 − Li1] − Li4) pathways by neutron powder diffraction combined with a maximum entropy analysis. Hence, they demonstrated that already at room temperature a quasi 3D diffusion mechanism is operative in LGPS, with the 3D character of Li diffusion further increasing at higher T [71,72] (Fig.…”
Section: (I) Structural and Electrochemical Propertiesmentioning
confidence: 84%
“…In particular, the nominal stability window may be different (likely smaller) for different solid solution members than currently available experimental data suggest [90]. Possible complications include the transformation of LGPS into orthorhombic thio-LISICON phases with different stoichiometry and the concomitant formation of side phases, as already observed for LGPS by the formation of Li 4 P 2 S 6 between 300 and 400°C [71]. As the authors of that study point out, however, it is well conceivable that the formation of decomposition products commences already near room temperature, which is particularly critical for the long-term operation of all-solid-state batteries based on LGPS.…”
Section: (I) Structural and Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) Lithium dendrites formation can be restrained, which allows the use of metallic lithium as anode due to the mechanically more robust nature of solid-state electrolytes. [23][24][25], and Li 10 GeP 2 S 12 [26][27][28], polymeric Li-ion conductors [12,29], (nitrogen doped) lithium phosphate (Li 3 PO 4 and LiPON) [30][31][32] and MeO-based oxides (LiNbO 3 [33], LiTaO 3 [34] and Garnets-type Li 7 La 3 Zr 2 O 12 [35][36][37]). Generally, lithium thiophosphates and complex sulfides have a moisture sensitive nature.…”
Section: Solid-state Electrolytesmentioning
confidence: 99%